2022
DOI: 10.3389/fphar.2022.728256
|View full text |Cite
|
Sign up to set email alerts
|

Chinmedomics Strategy for Elucidating the Pharmacological Effects and Discovering Bioactive Compounds From Keluoxin Against Diabetic Retinopathy

Abstract: Keluoxin (KLX) is an active agent in the treatment of diabetic retinopathy (DR). However, its mechanism, targets, and effective constituents against DR are still unclear, which seriously restricts its clinical application. Chinmedomics has the promise of explaining the pharmacological effects of herbal medicines and investigating the effective mechanisms. The research results from electroretinography and electron microscope showed that KLX could reduce retinal dysfunction and pathological changes by the DR mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Untargeted metabolomic analysis on serum was used to investigate the effect and mechanism of medicine or natural active components on DR as well (90). As an example, Kong et al discovered 64 serum biomarkers of DR in C57BL/KsJ-db/db mice based on the confirmed effectiveness of Keluoxin (KLX), 51 of which moved toward normal levels by KLX intervention, such as gamma-linolenic acid, L-tyrosine, L-tryptophan, L-phenylalanine, and others (98). By further analysis, six core metabolic pathways like tryptophan metabolism were deemed as vital ones significantly associated with the KLX effect on DR.…”
Section: Basic Researchmentioning
confidence: 99%
“…Untargeted metabolomic analysis on serum was used to investigate the effect and mechanism of medicine or natural active components on DR as well (90). As an example, Kong et al discovered 64 serum biomarkers of DR in C57BL/KsJ-db/db mice based on the confirmed effectiveness of Keluoxin (KLX), 51 of which moved toward normal levels by KLX intervention, such as gamma-linolenic acid, L-tyrosine, L-tryptophan, L-phenylalanine, and others (98). By further analysis, six core metabolic pathways like tryptophan metabolism were deemed as vital ones significantly associated with the KLX effect on DR.…”
Section: Basic Researchmentioning
confidence: 99%
“…However, the changes of IAA in serum level of DR have been rarely reported. Kong et al suggested that increasing the levels of tryptophan and IAA and decreasing the level of indole acetaldehyde by drugs may modulate tryptophan metabolism to protect the nervous system of T2DM samples (32). Besides, there was a human trial showed that oral IAA can reduce blood glucose in diabetic samples (33).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, six potential vasodilator compounds with relaxant effects on mesenteric arteries were selected using multivariate statistical analysis, including corynoxeine, isocorynoxeine, isorhynchophylline, rhynchophylline, and hirudin. Sun et al (2022) identified glycyrrhizic acid, kaempferol, cinnamaldehyde, catechin daidzein, and caffeic acid as the primary therapeutic efficacy components of Lingguizhugan decoction in the treatment of heart failure using UHPLC-Q-TOF-MS/MS in conjunction with cell experiments and digital storage mining; Kong et al (2022) used UPLC-QTOF-MS to explore the core active ingredients of Keluoxin (KLX) in the treatment of diabetic retinopathy. The results showed that rhein, astragaloside IV, emodin, chrysophanol and other compounds may be the pharmacodynamic basis of KLX.…”
Section: Pharmacophoric Substance Discoverymentioning
confidence: 99%